2018
DOI: 10.1093/carcin/bgy009
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of colorectal cancer by black raspberry anthocyanins involved the modulation of gut microbiota and SFRP2 demethylation

Abstract: Freeze-dried black raspberry (BRB) powder is considered as a potential cancer chemopreventive agent. In this study, we fed azoxymethane (AOM)/dextran sodium sulfate (DSS)-treated C57BL/6J mice with a diet containing BRB anthocyanins for 12 weeks, and this led to a reduction in colon carcinogenesis. These animals had consistently lower tumor multiplicity compared with AOM/DSS-treated mice not receiving BRB anthocyanins. In AOM/DSS-treated mice, the number of pathogenic bacteria, including Desulfovibrio sp. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 43 publications
1
72
0
Order By: Relevance
“…and Desulfovibrio sp. ), and at the same time to increase Eubacterium rectale , Faecalibacterium prausnitzii and other probiotic species populations in gut [ 61 ]. This gut microbiota modulation can explain the important differences described in this study between animals receiving both types of sausage diet.…”
Section: Discussionmentioning
confidence: 99%
“…and Desulfovibrio sp. ), and at the same time to increase Eubacterium rectale , Faecalibacterium prausnitzii and other probiotic species populations in gut [ 61 ]. This gut microbiota modulation can explain the important differences described in this study between animals receiving both types of sausage diet.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the chemopreventive activity of BRB anthocyanins involves induction of cell apoptosis and differentiation, and reduced cell proliferation, inflammation, angiogenesis and invasiveness (38) . The chemopreventive effect of BRB anthocyanins on CRC also appears to involve the modification of gut microbiota and DNA demethylation (39) . In this study, we have demonstrated for the first time that the chemopreventive effect of BRB anthocyanins against CRC might also involve the up-regulation of miR-24-1-5p, and we have shown this through the use of a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…These substances caused demethylation of the secreted frizzled related protein 2 (SFRP2) gene promoter, resulting in an increased expression of SFRP2, both at the mRNA and protein levels. In addition, they also down-regulated the DNMT31 and DNMT3B, and p-STAT3 expression (Chen L. et al, 2018).…”
Section: In Vivo Studiesmentioning
confidence: 96%